-3(p - 5) - 7p + 2(p - 18)
-3p+15-7p+2p-36
-8p-21
-8p=21
p=-21/8
2007-06-19 08:42:50
·
answer #1
·
answered by Tu N 2
·
0⤊
0⤋
Just multiply it out and add like terms. Remember, the biggest mistake most young math students make is the distributive property. The sign in front of a number always goes with it, and minus times a minus equals a plus. So, here's the first step: Multiply it out.
-3p +15 -7p +2p -36
Now, put like terms together and add like terms:
-3p-7p+2p + 15-36
-8p -21
2007-06-19 08:48:19
·
answer #2
·
answered by Scott W 3
·
0⤊
0⤋
-3(p - 5) - 7p + 2(p - 18)?
distrube, follow this formula:
a(b + c) = ab + ac
or a(b - c) = ab - ac
distribute the -3 and the 2
-3p -3(-5) - 7p + 2p - 2(18)
-3p + 15 - 7p + 2p - 36
combine like terms, but first rearrange the terms
-3p - 7p + 2p + 15 - 36
combine like terms
-8p - 21
2007-06-19 08:43:27
·
answer #3
·
answered by 7
·
0⤊
0⤋
-3(p - 5) - 7p + 2(p - 18)
-3p+15-7p+2p-36 add the p's
-8p+15-36
-8p-21
2007-06-19 08:51:21
·
answer #4
·
answered by English Wiz 4
·
0⤊
0⤋
-3p+15-7p+2p-36
= -8p-21 simply that all you need
if you need to find the value of p
if you let -8p-21=0
then p= -21/8
2007-06-19 08:45:42
·
answer #5
·
answered by cafet 1
·
0⤊
0⤋
= - 3p + 15 - 7p + 2p - 36
= - 8p - 21
= - (8p + 21)
2007-06-19 10:40:33
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
wl, simplified, it would be -3p + 15 - 7p + 2p -36 = -8p-21. Sorry if it's wrong!!
2007-06-19 08:44:51
·
answer #7
·
answered by tiannawoolf 2
·
0⤊
0⤋
-3(p-5)-7p+2(p-18)
=-3p+15-7p+2p-36
=-8p-21
2007-06-19 16:41:32
·
answer #8
·
answered by srirad 2
·
0⤊
0⤋
3p - 21
2007-06-19 08:42:07
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋